2020
DOI: 10.1080/20013078.2020.1809064
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from human iPSC‐derived neural stem cells: miRNA and protein signatures, and anti‐inflammatory and neurogenic properties

Abstract: Grafting of neural stem cells (NSCs) derived from human induced pluripotent stem cells (hiPSCs) has shown promise for brain repair after injury or disease, but safety issues have hindered their clinical application. Employing nano-sized extracellular vesicles (EVs) derived from hiPSC-NSCs appears to be a safer alternative because they likely have similar neuroreparative properties as NSCs and are amenable for non-invasive administration as an autologous or allogeneic off-theshelf product. However, reliable met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(163 citation statements)
references
References 103 publications
4
145
0
Order By: Relevance
“…Three similar studies to ours in rodent brain tissue found that within 2 and 6 h after intranasal administration, EVs were widely distributed into the somatosensory and prefrontal cortex, amygdala, dentate gyrus, and cerebellum [65,66]. Similar to our findings, EVs were in neurons, microglia, and astrocytes [66], and completely cleared from brain within 24 h [67].…”
Section: Discussionsupporting
confidence: 89%
“…Three similar studies to ours in rodent brain tissue found that within 2 and 6 h after intranasal administration, EVs were widely distributed into the somatosensory and prefrontal cortex, amygdala, dentate gyrus, and cerebellum [65,66]. Similar to our findings, EVs were in neurons, microglia, and astrocytes [66], and completely cleared from brain within 24 h [67].…”
Section: Discussionsupporting
confidence: 89%
“…Exosomal miRNAs and proteins isolated from hiPSC-NSC cultures have many functions, such as neuroprotection and anti-inflammation. The intranasal administration of exosomes can be absorbed by a variety of nerve cells, which is beneficial for brain repair after injury or disease ( 139 ). A separate study showed that secreted exosomes coated with miR-146a-5p from MSCs relieved Group 2 innate lymphoid cells (ILC2s) in innate airway inflammation, showing significant advantages of low immunogenicity and high biosafety ( 140 ).…”
Section: Clinical Application Of Exosomal Ncrnasmentioning
confidence: 99%
“…Exosomes have a natural ability to cross the normal, unperturbed blood–brain vascular barrier [ 95 , 96 , 97 ] by transcytosis [ 95 , 224 ], thus enabling the systemic treatment of CNS-inflammatory disorders [ 238 ] and possibly cancers [ 239 ], even when administered by the nasal route [ 238 , 240 , 241 , 242 ].…”
Section: Advantages Of Therapy With Natural Exosomes Vs Artificiamentioning
confidence: 99%
“…There is a revolutionary ability to administer exosomes via the nasal route. These exosomes then traffic around cranial nerve I fibers for smell, via the cribriform plate of the skull, to transit into the brain for the treatment of neuro-inflammatory conditions [ 246 ], like models of viral encephalitis and multiple sclerosis [ 246 ], brain injury [ 238 , 241 ], and even attempts to treat a mouse model of autism [ 242 ] and prevent brain damage from epilepsy [ 240 ]; interestingly, even when given via a nasal spray is sufficient [ 241 ]. The further exploitation of the exosome nasal route of administration may treat brain tumors [ 235 ] and spinal cord injury [ 239 ] or can be directed at airway inflammation [ 247 ], chronic rhinosinusitis [ 248 ], and possibly COVID-19 lung infections.…”
Section: Advantages Of Therapy With Natural Exosomes Vs Artificiamentioning
confidence: 99%